HIV CASES AND POPULATION DENSITY (WITH SPATIAL ANALYSIS APPROACH) - Lase, Krisologus; Dertiana Sianturi; Wita Permata Sari Gulo; Vierto Irennius Girsang, (Mitra Husada Health Internasional Conference (MIHHICo), 2024)
The HIV epidemic has become a major health problem worldwide. Human Immunodeficiency Virus is an infectious disease whose number of sufferers continues to increase. Its spread extends from major cities to remote villages. The purpose of the study is to determine the relationship between the incidence of HIV cases and population density in North Sumatra province per city district with a spatial analysis approach. The study design used is an ecological study using aggregate analysis units. The data used is new HIV cases per district/city sourced from the BPS website of North Sumatra province in 2022. Population density data is taken from the BPS website of North Sumatra province in 2022, dividing the number of people per city district by the area of the area. The distribution of high-category HIV cases in North Sumatra is in 4 district/city, namely Simalungun, Asahan, Deli Serdang and Medan City, while the distribution of medium category HIV cases in district/city in 2022 is in 24 district/city and the HIV distribution category where there are no cases is 5 districts/cities. The distribution of population density in the dense category in North Sumatra province is found in 4 district/city while the distribution of population density in the rare category in North Sumatra province in 2022 is found in 25 district/city and 4 district/city with low population density. There is no relationship between population density and HIV cases in North Sumatra Province.